Governing the Market through Fatwa: The Political Economy of the Indonesian Ulema Council’s Fatwa on the Prioritization of Domestic Products - Edi Kurniawan (Letiges, 2026)
Studies on the Indonesian Ulema Council’s fatwas have continued to expand; however, they rarely conceptualize fatwas as instruments of hybrid regulation operating within the political economy of the modern nation-state and functioning as soft law with the capacity to shape market dynamics. In particular, Fatwa No. 14/Ijtima’ Ulama/VIII/2024 on the Priority Use of Domestic Products—together with its maqāṣid al-sharīʿah (the objectives of Islamic law) foundations and its political–economic implications within the framework of Indonesian economic nationalism—has received limited scholarly attention. This study addresses this gap by analyzing the fatwa as a model of ijtihād in Islamic economic governance that integrates maqāṣid al-sharīʿah and the political economy of religion within a unified analytical framework. Employing a qualitative socio-legal methodology, this research conducts close reading and thematic coding of the official fatwa text, relevant regulations promoting domestic products, and pertinent academic literature. The study demonstrates that the fatwa explicitly links the prioritization of domestic products to ḥifẓ al-māl (the protection of wealth), maṣlaḥah ʿāmmah (public welfare), and economic sovereignty, thereby reconstructing consumption at the normative level from a neutral individual preference into a collective moral obligation. Within this framework, the fatwa functions as non-state soft law that symbolically directs market preferences toward local producers, distributes symbolic capital to aligned economic actors, and supports the state’s economic nationalism agenda, while simultaneously leaving unresolved risks related to symbolism, structural inequality, and ethical blind spots. This study offers a conceptual lens for understanding fatwas as instruments of Islamic economic governance that mediate between sharia norms, state policy, and market dynamics in contemporary Indonesia.